2019
DOI: 10.1103/physreva.99.052350
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of randomized benchmarking

Abstract: Randomized benchmarking and variants thereof, which we collectively call RB+, are widely used to characterize the performance of quantum computers because they are simple, scalable, and robust to state-preparation and measurement errors. However, experimental implementations of RB+ allocate resources suboptimally and make ad-hoc assumptions that undermine the reliability of the data analysis. In this paper, we propose a simple modification of RB+ which rigorously eliminates a nuisance parameter and simplifies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…A similar method was explored in Ref. [12] to reduce the fitting parameters in order to derive multiplicative precision in standard RB. In addition to both of these advantages, we find that it also allows us to separate the analysis of the standard decay r from the effects of leakage errors and reduce the assumptions required in the derivation.…”
Section: Subspace Randomized Benchmarkingmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar method was explored in Ref. [12] to reduce the fitting parameters in order to derive multiplicative precision in standard RB. In addition to both of these advantages, we find that it also allows us to separate the analysis of the standard decay r from the effects of leakage errors and reduce the assumptions required in the derivation.…”
Section: Subspace Randomized Benchmarkingmentioning
confidence: 99%
“…Subgroups of Pauli/Weyl gates, e.g. {1, X}, will also fix the asymptote [12] but will require additional assumptions for the leakage analysis. In RB, we estimate p( ) for different values of and fit the results to Eq.…”
Section: Appendix B: Standard Randomized Benchmarking Derivationmentioning
confidence: 99%
“…We run mirror benchmarking on n = 6, 8, 10 qubits. For the largest circuits run in this experiment, with n = 10 and sequence length L = 16, corresponding to a two-qubit circuit depth of 32 and 160 total two-qubit gates, we obtain an average survival probability of 0.344 (18). The outline of this paper is as follows.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that varying the number of sequences depending on Clifford length may improve the reliability of estimated decay rate [16]. Finding the best maximum Clifford length was also discussed in [17]. However, none of them addressed the problem of both optimizing Clifford lengths and the number of sequences at the same time.…”
Section: Introductionmentioning
confidence: 99%